Application of Floquet's Method to High-Speed Train/Track Dynamics - T. Krzyżyński (Engineering Transactions)
The paper deals with the vertical dynamics of a railway track and a guideway for the magnetic high-speed system with contact-free levitation technology (Maglev). The conventional railway track is composed of rails mounted on the equally spaced sleepers which rest on the ballast, with a pad between the rail and sleeper. The guideway for Maglev system is composed of simply supported girders which are mounted on piers. Usually, the span of adjacent girders is equal and the guideway is composed of repetitive elements mounted with high positional accuracy. The track as well as the guideway form typical periodic systems which consist of a number of identical flexible elements coupled in an identical way. In the paper the free wave propagation problems and the steady-state system dynamic responses to a moving harmonic force are considered. In both cases the solution method proposed consists in the direct application of Floquet's theorem to the differentia! equations of motion of the periodic systems.